COMPARATIVE ANALYSIS OF THE MAIN PROVISIONS OF NON-JUDICIAL AND JUDICIAL EXAMINATION OF CONSTRUCTION FACILITIES DESIGN DOCUMENTATION - AMINEV Farit Gizarovich; ZAMYATIN Sergey Alexandrovich (Правовое государство: теория и практика, 2024)
The urgent task of forensic expert science is the development of methodological bases of judicial examination of construction facilities design documentation, which differ from the methodological provisions of non-judicial state (or non-state) examination of design documentation. Purpose: to undertake a comparative analysis of judicial examination of construction facilities design documentation and non-judicial examination of design documentation carried out in accordance with Article 49 of the Town Planning Code of the Russian Federation. Methods: empirical methods of comparison, description, mathematical calculations; theoretical methods of formal and dialectical logic; specific scientific methods of modeling and interpretation of legal norms. Results: the article develops and formulates the definitions of the basic concepts of judicial examination of design documentation. On the basis of comparative analysis, the authors identify some analogies and differences in the tasks and methods of research in the procedure for conducting judicial and nonjudicial examination of construction facilities design documentation. The article considers procedural features of the application of existing norms to the composition, content and presentation of design documentation as well as to the calculation substantiation of design decisions. Some problems of carrying out judicial examination of construction facilities design documentation are revealed: insufficient level of qualification of forensic experts; errors related to misunderstanding of the subject, purpose and objectives of forensic examinations. The necessity and specifics of individualization of design documentation in the course of judicial and non-judicial expert examination of construction facilities design documentation are noted. It is established that the basis for a forensic report is the assessment of the impact of non-compliance of design solutions with the normative rules on the reliability of the designed structure. Methodological recommendations are developed for assessing construction facilities design documentation.